FLOUTING MAXIM IN FAMILYS COMMUNICATION AT HOME DOMAIN - Sitorus, Nurhayati; Siagian, Beslina Afriani (Premise: Journal of English Education and Applied Linguistics, 2023)
This research aims to investigate the tpe of flouting maxim that occurs on family’s communication at home domain. The design of this research used descriptive qualitative research. People who did communication at the writer’s home as the subject of this research. The data was collected by using observation, recording the conversation and using field note. Then data was analyzed by using Miles and Huberman Model that consisted three stage, namely data reduction, displaying data and drawing conclusion/verification. The result of the study shows that there are four types of flouting maxim that occurred in family’s communication at home, namely flouting maxim in quality, flouting maxim in quantity, flouting maxim in relevance, and flouting maxim in manner. In doing communication, the flouting maxim is done to get intention and purpose.